Building Student Character Through Role Models in The MABIT Program at SDIT Al-Hikmah Banjarmasin - Sa’idah, Siti; Norsiva, Norsiva; Sholeh, Makherus (Ta'allum: Jurnal Pendidikan Islam, 2024)
Character education is one of the crucial aspects in shaping students' personalities, especially in the modern era that is full of moral and social challenges. One of the practical approaches in character education is role modeling, where teachers and parents act as examples of good behavior by moral and spiritual values. In this context, the Malam Bina Iman dan Taqwa (MABIT) program at SDIT Al-Hikmah Banjarmasin offers an integrated method to improve student character through exemplary behavior demonstrated by teachers as well as the active involvement of parents. This study aims to analyze the effectiveness of the MABIT program in improving student character. This research uses a qualitative case study approach with data collection techniques through observation, in-depth interviews, and documentation. The informants totaled 13 people who were directly involved in MABIT activities. The results showed that the MABIT program, which involves congregational prayers, Qur'anic tadarus, inspirational film screenings, devotional sessions, and reflections, improved student character, especially in strengthening discipline, religiosity, and moral values. The role of teachers as role models and parents' involvement contribute significantly to this program's success. By showing exemplary worship practices and discipline, teachers became positive models for students. Parents' participation in supporting MABIT activities also strengthens the internalization of these values at home. Based on these findings, the study recommends developing various activities to enrich students' experiences and increasing parental involvement to strengthen the program's positive impact on students' character-building.